Perubahan Penggunaan Lahan Dan Dampaknya Terhadap Erosi Di Daerah Aliran Sungai Wae Lela Kota Ambon - Rambli Buton; Ruddy Soplanit; Agusthinus Jacob (Agrologia, 2016)
High population of inhabitans in watershed area is an important factor which increase watershed’s damage so that, proper land conservation should be done. Research in the watershed Wae Lela has been done to analyze the dominant factors causing soil erosion due to changes in land use, and determine the amount of erosion after land use change in the watershed. The research method was field survey with a synthetic approach pattern by using free surveys observation distance. This observation distance used according to the pattern of land use changes on certain land units, with the type of profile observations/boring. The study found that land use in the watershed Wae Lela has undergone considerable changes in the last 25 years between 1988-2013. Natural forest generally has been transformed to be used for landfarming. Fram planted with multiple cropping of cloves, nutmeg, coconut, tubers, vegetable was become less effective to prevent erosion. This change leads to increased erosion which mainly occurred in mixed farm area up to  6415.06 t/ha/year; covered an area of  220.6 ha or 26.2% of the research area.